2017
DOI: 10.1016/j.bjan.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Bloqueio do quadrado lombar em dor crônica pós‐hernioplastia abdominal: relato de caso

Abstract: We consider that performing the quadratus lumborum block type II was an important analgesic option in the treatment of a patient with chronic pain after abdominal hernia repair, emphasizing the effects of local anesthetic spread to the thoracic paravertebral space. The technique has proven to be safe and well tolerated. The publication of more clinical cases reporting the effectiveness of this blockade for chronic pain is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 5 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…4 In the past few years, several case reports have shown that the QLB has also been successful in providing postoperative pain relief. [5][6][7][8] In a previous randomized control study, we compared the QLB against a control group, in which we intentionally moved our point of injection from the original anterolateral side of the quadratus lumborum muscle to the posterior wall (QLB type 2). 9 This has become our standard practice, as we have abandoned the anterolateral approach completely subsequent to publication of our magnetic resonance study on optimal point of insertion and dispersion of local anesthetics.…”
mentioning
confidence: 99%
“…4 In the past few years, several case reports have shown that the QLB has also been successful in providing postoperative pain relief. [5][6][7][8] In a previous randomized control study, we compared the QLB against a control group, in which we intentionally moved our point of injection from the original anterolateral side of the quadratus lumborum muscle to the posterior wall (QLB type 2). 9 This has become our standard practice, as we have abandoned the anterolateral approach completely subsequent to publication of our magnetic resonance study on optimal point of insertion and dispersion of local anesthetics.…”
mentioning
confidence: 99%
“…Single injection QL block has been used successfully for the management of postoperative pain relief after caesarean section [12] for sub-total gastrectomy in a septic patient [13], laparotomy for duodenal tumour excision and to manage chronic back pain [14]. The effective pain relief lasted for 12-14hours.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Various case reports are there showing effective post-operative analgesic profile of QL block. [49101112]…”
Section: Introductionmentioning
confidence: 99%